Syntax Error on Written Language in Bipa Program: A Study on Cambodian Students at Widyatama University Bandung, Indonesia - Heryono, Heri; Surtia Zulpratita, Ulil; Yuliani, Sy.; Rosita, Ai (International Journal of Psychosocial Rehabilitation, 2020)
Bahasa Indonesia becomes one of the most favored languages for foreigners, especially in Asia. Though the language has a similar root as Malay, Singapore, and several Southeast Asian countries, Indonesia attracts more foreigners for some reasons. The study of Bahasa Indonesia for foreigners is called BIPA, Bahasa Indonesia untuk Penutur Asing. This program has continually developed since the beginning of its appearance. Foreigners who come to Indonesia for various purposes, such as traveling, business, or even studying in some institutions. One of the institutions that accepted foreigners as students was Widyatama University Bandung. They collaborated with NPIC (National Polytechnic Institute of Cambodia) to have a joint degree program in 2017 (batch I) and in 2018 (batch II). Students tended to make some mistakes in the learning process. The errors were attributable to their native language (Khmer), which was basically different with Bahasa Indonesia. During the learning process in the BIPA program, syntax errors occurred, especially in written language, when they sent information through social media (instant messaging), such as WhatsApp or Line. The research was conducted at Widyatama University during a four-month program. The research focused only on the syntax level, and this study was qualitative research in the form of a case study.